Impacts of Industrial Wastewater Effluent on Ekerekana Creek and Policy Recommendations for Mitigation - Ogechi Amanda Onukogu; Chisom N. Onyebuchi; Temiloluwa O. Scott; Tolulope Babawarun; Chukuneye Neye-Akogo; Olusegun A. Olagunju; Chinedum Gloria Uzougbo (The Journal of Engineering and Exact Sciences)
This study investigated the impact of industrial wastewater originating from the Port-Harcourt Refinery Company Limited on Ekerekana Creek in Rivers State, serving as a primary fishing source for various communities. Water samples were collected and tested using established laboratory techniques, focusing on parameters such as heavy metals, pH levels, Phosphate, Nitrate, Temperature, Dissolved Oxygen, and BOD5. The findings revealed varying concentrations of heavy metals and other parameters in the water samples, with the highest concentrations observed at the discharge point (station 2), negatively affecting the flora population. The values of most parameters analyzed were below NESREA/WHO standards; however, the results underscore the importance of proper wastewater treatment and management from industrial sources to protect the environment and ensure the health and well-being of communities that rely on the creek.Based on the study's findings and best practices from the UK, US, and France, a set of comprehensive policy directions and community social responsibility measures are proposed. These recommendations include proper treatment of effluent by the Port-Harcourt Refinery Company Limited before discharge, active regulatory agency involvement, the adoption of an efficient and modern wastewater treatment facility, and the initiation of a clean-up procedure to reduce heavy metal concentrations and mitigate environmental hazards. Additionally, we advocate for the establishment of collaborative partnerships, community engagement, integrated watershed management, enforcement and compliance, research and innovation, and climate change adaptation and resilience measures. Implementing these recommendations will contribute to lasting improvements in water quality and the overall health of Ekerekana Creek and its surrounding communities.